Spectrophotometric assays for total antioxidant capacity (TAC) in dog serum: an update. Issue 1 (December 2016) - Rubio, Camila; Hernández-Ruiz, Josefa; Martinez-Subiela, Silvia; Tvarijonaviciute, Asta; Ceron, José
Abstract The aim of this review is to study the main spectrophotometric methods used to evaluate total antioxidant capacity (TAC) in serum samples of dogs. Total antioxidant capacity (TAC) is an analyte frequently used to assess the antioxidant status of biological samples and can evaluate the antioxidant response against the free radicals produced in a given disease. Trolox equivalent antioxidant capacity (TEAC), ferric reducing ability of plasma (FRAP), and cupric reducing antioxidant capacity (CUPRAC) are different assays described to determine TAC of a sample. This review explains the basis of each assay and their application in the determination of TAC in dogs, and also provides selected information about reports in humans for comparative purposes. It is concluded that, ideally, various different assays integrated in a panel should be used for TAC evaluation, since depending on the assay performed TAC results can be markedly different.